COPING STRATEGIES FOR THE ELDERLY IN DEALING WITH FAMILY RELATIONSHIP GAP IN PEKIK NYARING VILLAGE - Meita Relinza; Tamrin Bangsu; Ishak Fadlurrohim (Universitas Negeri Medan, 2025)
The increase in life expectancy in Indonesia, including in Central Bengkulu, has caused the number of elderly people to continue to increase and their need for family social support is getting higher. In Pekik Nyaring Village, some elderly people face gaps in relationships with their families due to distance from their homes, infrequent communication, and reduced emotional attention. This situation leads to loneliness, worry, and decreased psychological well-being. This research aims to uncover the coping strategies used by the elderly in dealing with family relationship gaps. The approach used is qualitative descriptive with purposive sampling technique. Six elderly people were selected as informants, and data was collected through in-depth interviews and observations. The analysis process includes data reduction, data presentation, and conclusion drawn. The results of the study showed that the elderly applied two forms of coping strategies, namely problem-focused coping and emotion-focused coping. Problem-focused coping can be seen from the efforts of the elderly to fill their time with productive activities, interact with the surrounding environment, and participate in religious activities. Meanwhile, emotion-focused coping is seen through the attitude of accepting the situation, trying to be patient, managing emotions, and strengthening spirituality through prayer, reading the Qur'an, and dhikr. These findings emphasize the importance of family support and social environment to support the emotional well-being of the elderly and serve as a reference in the preparation of more targeted social interventions. Keywords: Elderly, Relationship Gap, Coping Strategy